COMMUNICATION STRATEGY OF SAUNG ALAM BURUAN AJAR INDONESIA AS A MEDIUM FOR SUNDANESE CULTURAL LEARNING AMONG CHILDREN - Salim, Ahmad Agus; Hildawati, Hildawati (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Saung Alam BAI not only aims to provide access to education but also plays a role in preserving local culture, particularly Sundanese culture. This effort is crucial to ensure that children not only receive basic education but also understand and appreciate their local heritage. This research aims to analyze the communication strategy applied by Saung Alam Buruan Ajar Indonesia in learning Sundanese culture among children. Using a qualitative approach, this study collected data through interviews and on-site observations. The results show that effective communication strategies include the use of interactive media, experiential teaching, and community engagement. The research recommends further development of learning methods that integrate technology and local culture to enhance children's understanding of Sundanese cultural heritage.